EFEKTIVITAS INTERVENSI KOMPRES ALOEVERA TERHADAP PENURUNAN SUHU TUBUH ANAK FEVER DI PUSKESMAS BAHBIAK KOTA PEMATANGSIANTAR KEC. SIANTAR MARIMBUN TAHUN 2020 - dewi tiansa barus (Jurnal Penelitian Keperawatan Medik, 2020)
Fever in children is a condition that often causes serious problems in children. Fever occurs at temperatures >37.5ºC usually caused by autoimmune infections and diseases. The World Health Organization (WHO) states that the number of diseases in children with fever symptoms is 62% with a mortality rate of 33%. Giving Aloe Vera compresses is one of the non-phamacological interventions that can reduce dampness. The purpose of this study was to find out how the effectiveness of Aloe Vera Compress Intervention on Decreasing body temperature in children with fever. The research design used One group pretest-posttest. The variables in this research are Aloe Vera Compress as an independent variable and Decrease in body temperature in Fever children as the dependent variable. The population in this study were all pediatric patients aged 5-11 years who experienced fever at the Bahbiak Health Center in Pematangsiantar City, Siantar Marimbun District. Sampling using purposive sampling technique of 12 respondents. The intervention carried out compresses Aloe Vera for 15 minutes. Temperature measurement using a digital thermometer. Data were collected by observation sheets and tested by Paired Sample-Test. The results showed that there was a change in the body temperature of the Fever child. The results of Shaphiro-Wilk normality test results of body temperature before giving Aloe Vera compress is 130 and body temperature after giving Aloe Vera compress is 037. Paired Sample-Test statistical test results show data ρ = 0,000 <α = 0.05 then Ho is rejected and Ha is accepted. which means that there is an effectiveness in administering Aloe Vera compresses to reduce body temperature of children aged 5-11 years of fever. It is hoped that health workers can apply non-pharmacological therapies such as aloe vera compresses for a decrease in a child's body temperature.